1996
DOI: 10.1126/science.274.5292.1486
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Zonal Displacements of the Pacific Warm Pool: Implications for ENSO

Abstract: The western equatorial Pacific warm pool is subject to strong east-west migrations on interannual time scales in phase with the Southern Oscillation Index. The dominance of surface zonal advection in this migration is demonstrated with four different current data sets and three ocean models. The eastward advection of warm and less saline water from the western Pacific together with the westward advection of cold and more saline water from the central-eastern Pacific induces a convergence of water masses at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
237
2
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(265 citation statements)
references
References 24 publications
18
237
2
8
Order By: Relevance
“…These Kelvin waves initiate the relaxation of the zonal sea level and thermocline gradients, followed by advection of the western equatorial warm pool into the central Pacific. The warmer waters, usually defined as greater than 28øC [Picaut et al, 1996] are very low in nutrients [Mackey et al, 1995], especially NO3. Their advection over the central region of the Pacific, combined with the cessation of upwelling leads to dramatically reduced phytoplankton productivity in the equatorial Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…These Kelvin waves initiate the relaxation of the zonal sea level and thermocline gradients, followed by advection of the western equatorial warm pool into the central Pacific. The warmer waters, usually defined as greater than 28øC [Picaut et al, 1996] are very low in nutrients [Mackey et al, 1995], especially NO3. Their advection over the central region of the Pacific, combined with the cessation of upwelling leads to dramatically reduced phytoplankton productivity in the equatorial Pacific.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, because of evaporation and equatorial upwelling, the cold tongue is composed of high salinity water. Recently, it was found that the water masses of these two regions converge zonally into a well-defined salinity front [Picaut et al, 1996]. This convergence also leads to the formation of the barrier layer [Lukas and Lindstrb'm, 1991] in the isothermal layer of the warm pool [Vialard and Delecluse, 1998b].…”
mentioning
confidence: 99%
“…In other words, the selection of NINO3 may be justified by the perturbation theory for a coupled atmosphere-ocean model, even if Yang et al (2006) results may be strongly model dependent. From an observational point of view, the eastern edge of the warm pool in the central Pacific seems to be where the atmospheric response is the strongest (e.g., Palmer and Mansfield 1984;Kessler et al 1995;Picaut et al 1996). However for the selection of El Niño years, NINO3 or NINO3.4 SST give the same result.…”
Section: Indicesmentioning
confidence: 56%